An Analysis of the library usage patterns of U.P. College of Home Economics students of the College of Home Economics Library - Datoy, Harley Jes A.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
This study aimed to analyze and assess the library usage patterns of the College of Home Economics students and to determine the factors that influence it. It also aimed to determine if there is a relationship between personal attributes such as age, gender, civil status, year level, course and distance of residence from the UP Campus. External factors such as the library's resources, services, and facilities were also studied if they have a significant effect on the students' library usage patterns.
In addition, this study also aimed to assess the College of Home Economics students' perception on their library's resources, services, and facilities. This study also aimed to determine the problems encountered by students when using the College of Home Economics Library.
A descriptive quantitative approach was used to determine the library usage patterns of the U.P. College of Home Economics students. Survey questionnaires were the main tool in gathering data. Personal interviews were also conducted in addition to the researcher's personal observations. Statistical methods were used to analyze the collected data thus statistical programs such as SPSS and Microsoft Excel were used. The researcher used the Slovin's Formula to determine the sample size of the study. The sample size of the study was 293 questionnaires handed out, only 262 were returned. The survey questionnaires was divided into 4 categories: personal information, library usage, library service, and library collection and services.
The findings of the study show the library usage patterns of U.P. College of Home Economics students. The study revealed that a student's course, professor, and library ambiance has a significant effect on the student's library usage patterns.
Several recommendation were formulated based from the findings of the study to further improve the library and the students' library usage patterns. Recommendations were suggested to further meet all of the students' library needs.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines(Diliman) -- College of Home Economics -- Students; Library use studies; Libraries -- User satisfaction